Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada Hotel Khas Pekanbaru - Harwina, Yulia; Swara, Dinda Genta (Eko dan Bisnis: Riau Economic and Business Review, 2025)
The location of this research was conducted at the Pekanbaru Special Hotel located at Jl. Jend. Sudirman No.455, Simpang Empat, Pekanbaru City District, Pekanbaru City, Riau.Pekanbaru. This study aims to determine the Effect of Work Discipline on Employee Performance at the Pekanbaru Special Hotel. In analyzing the data obtained from the research object using quantitative analysis and the number of respondents 58 people, using the SPSS program using the Simple Linear Regression Analysis method. From the results of the regression in this study, the regression equation can be seen as follows: Y = 8.074 + 0.783X, This means that the value of a is 8.074, this value indicates that when the price variable (variable X) is zero, then the consumer decision on (variable Y) is 8.074. While the value of b is 0.783, meaning that when there is an increase in the value of the work discipline variable (variable X) by 1 (one) unit, then employee performance on (variable Y) will increase by 0.783 units. The calculated t value is 9.566. While the critical value according to the table with a significant level of 5% using the t table formula (α / 2; n-k) k = 2 and n = 58-2 = 56 is 2.00324, because t count> t table then Ho is rejected. This means that there is an influence by the Work Discipline variable on the employee performance variable. With the meaning of the word Hypothesis (Ha) is accepted. The positive calculated t value indicates that the work discipline variable has a unidirectional relationship with employee performance at the Pekanbaru Typical Hotel. The coefficient of determination (R Square) value is 0.620 or 62.0%, so it can be concluded that the Work Discipline variable is 62.0%, while the remaining 30.8% (100% -62.0%,,) is influenced by other factors that were not examined in this study